2013
DOI: 10.1193/1.4000113
|View full text |Cite
|
Sign up to set email alerts
|

Tohoku Tsunami-Induced Building Failure Analysis with Implications for U.S. Tsunami and Seismic Design Codes

Abstract: The structural details of numerous damaged buildings in the Tohoku region were documented soon after the 11 March 2011 Tohoku-oki earthquake and tsunami by a reconnaissance team sponsored by the American Society of Civil Engineers. Tsunami flow depths and velocities were determined based on analysis of video records and the observed effects on simple benchmark structures in the flow. Equations for various conditions of fluid loading were then validated through failure analyses completed for several buildings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…No pile remained connected to the pile caps, suggesting a higher level of shear in the overturning motion than was experienced in the other overturned building with a pile foundation (Fraser et al, 2013). This building was lifted by the hydrostatic buoyancy off of its pile foundation, which did not have tension capacity due to the minimal reinforcing steel (Chock et al, 2013). In addition, it was lifted off its original site and carried over a low wall before being deposited approximately 15 m inland from its original location (Chock et al, 2013).…”
Section: Building Dmentioning
confidence: 99%
See 1 more Smart Citation
“…No pile remained connected to the pile caps, suggesting a higher level of shear in the overturning motion than was experienced in the other overturned building with a pile foundation (Fraser et al, 2013). This building was lifted by the hydrostatic buoyancy off of its pile foundation, which did not have tension capacity due to the minimal reinforcing steel (Chock et al, 2013). In addition, it was lifted off its original site and carried over a low wall before being deposited approximately 15 m inland from its original location (Chock et al, 2013).…”
Section: Building Dmentioning
confidence: 99%
“…This building was lifted by the hydrostatic buoyancy off of its pile foundation, which did not have tension capacity due to the minimal reinforcing steel (Chock et al, 2013). In addition, it was lifted off its original site and carried over a low wall before being deposited approximately 15 m inland from its original location (Chock et al, 2013).…”
Section: Building Dmentioning
confidence: 99%
“…Tsunami-induced forces on buildings have never been directly measured, and although some studies have attempted to estimate tsunami forces from observed damage to onshore structures (Tokyo University and BRI, 2011;Chock et al, 2013), force-related TIMs for fragility analysis have always been based on numerical inundation modeling.…”
Section: Field Surveysmentioning
confidence: 99%
“…Furthermore, overtopping tsunami flow should be considered when establishing the required building height for designated evacuation buildings. Based on observed and possible future damage, new concepts can be proposed for the tsunami design codes of designated evacuation buildings to protect against earthquakes and subsequent tsunamis [Chock et al, 2013]. For existing evacuation buildings, strengthening plans should be implemented so that the buildings conform to the design criteria of tsunami design codes.…”
Section: Design Recommendation For Evacuation Buildingsmentioning
confidence: 99%